INVESTIGATING THE IMPACT OF INTERNAL AUDIT COMPETENCE AND QUALITY ON BANK PERFORMANCE - Gunawan, Henry (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
Banking is a highly regulated industry. Hence, it must comply with the regulations. To ensure compliance, an internal audit must exist. This study aims to check and analyze three associated impacts. The first and second are the effects of internal audit competence (IAC) on internal audit quality (IAQ) and bank performance (BP). The third is the influence of IAQ and BP. The population comes from the internal auditors of banks in Jakarta. Because of employing the quantitative approach, this study utilized at least 200 people as the sample. Advantageously, it can obtain 205 auditors based on the snowball sampling technique. Hence, the structural equation model based on covariance is applicable. After processing and examining their response, this study demonstrates that the model fits the data and concludes that (1) IAC and IAQ are positively related, (2) IAC and BP are positively associated, and (3) IAQ and BP are positively connected. Operationally, this study suggests that banks train their internal auditors by inviting experts, aiming to find deviations; therefore, the heads of related departments can fix them. If all departments can do it, the bank will perform well.